Young-Onset Ischemic Colitis: A Condition of Elusive Etiology Frequently Associated With Immune Dysregulation. (June 2020) - Byrnes, Kathleen; Khararjian, Armen; Mannan, Abul A. S. R.; Arnold, Michael; Voltaggio, Lysandra
Ischemic colitis (IC) associates with older age, hypertension, and heart disease, among others. Young-onset IC is rare. We aimed to delineate clinical characteristics of young patients (<40 years) with IC. Cases from 1984 to 2017 were re-reviewed. Of the 60 cases available, 52% (n = 31) had histologic features of IC. Fifty-five percent were female with a mean age of 32 (range = 14-40) years. Fifty-eight percent (n = 18) were resections. The most common presentations were diarrhea and abdominal pain. Three teenagers had IC associated with prior surgery, volvulus, and constipation. In the 21- to 40-year group, 43% (n = 12) lacked clinical associations. A second subset (n = 6, 21%) had histories of immune dysregulation (lupus, dermatomyositis, vasculitis) and poorly controlled HIV/AIDS (n = 5, 18%). Smoking and cocaine were endorsed by 1 and 2 patients, respectively. One patient had premature atherosclerosis while another had HMG Co-A lyase deficiency. Vasculitis was identified in 22% of the resections and in none of the biopsies. Nineteen percent of patients died (n = 6) from complications of IC, all treated surgically, including 1 patient previously misdiagnosed as ulcerative colitis; 2 patients died of unrelated causes. While rare before 20 years of age, IC in teenagers relates to mechanical issues and is rare in children. Associations in young adults include immune dysregulation, cocaine and cigarette use, and premature atherosclerosis. Our retrospective cohort had a surgical mortality rate within the range reported by others, highlighting the importance of accurate diagnosis in young individuals.